Social Mobility in Germany - Majed Dodin; Sebastian Findeisen; Lukas Henkel; Dominik Sachs; Paul Schüle (Center for Economic Studies and ifo Institute (CESifo), 2021)
We characterize intergenerational mobility in Germany using census data on educational attainment and parental income for 526,000 children. Our measure of educational attainment is the A-Level degree, a requirement for access to university. A 10 percentile increase in the parental income rank is associated with a 5.2 percentage point increase in the A-Level share. This parental income gradient has not changed for the birth cohorts of 1980-1996, despite a large-scale policy of expanding upper secondary education. At the regional level, there exists substantial variation in mobility estimates. Place effects, rather than sorting of households, account for most of these differences.
Keywords: I24; J62; R23; 330; intergenerational mobility; educational attainment; local labor markets